Comparative Evaluation between Visual and Automated Dipstick Urinalyses in Dogs - Erasmia D. Smyroglou; Labrini V. Athanasiou; Rania D. Baka; Zoe S. Polizopoulou (Veterinary Sciences, 2023)
Urine test strips are commercially available and can be assessed with semi-automated analyzers or by visual assessment. This study aimed to compare the visual and automated evaluations of dipstick variables in canine urine samples. One hundred and nineteen urine samples were evaluated. Automated analysis was performed on a veterinary urine analyzer URIT-50Vet (URIT Medical Electronic) with UC VET13 Plus strips. Multistix 10 SG dipsticks (Siemens Healthcare GmbH, Erlangen, Germany) were used for visual evaluation, along with a refractometer (Clinical Refractometer Atago T2-Ne, Atago Co., Tokyo, Japan) for urine specific gravity measurements. A linear relationship was observed between the pH measurements (p = 0.2) of the two methods; the Passing–Bablok procedure was valid since neither proportional nor systematic significant errors were observed. Comparing the two methods, the correlation for urine specific gravity was poor (p = 0.01, CI 0.667–1.000). Moderate agreement was demonstrated for proteins (κ = 0.431), bilirubin (κ = 0.434) and glucose (κ = 0.450). Agreement was substantial for blood (κ = 0.620) and poor for leukocytes (κ = 0.100). Poor agreement was observed for ketones (κ = −0.006). Apart from the pH analysis, visual and automated dipstick urinalyses should not be used interchangeably. Multiple urine samples obtained from the same dog during the day should be evaluated using the same method to overcome erroneous results.